2018
DOI: 10.1021/acs.macromol.8b01171
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Structure and Electromechanical Behaviors of Aliphatic Polyurethane Elastomers

Abstract: Understanding the relationship between multiphase structure and electromechanical property of thermoplastic dielectric elastomers is significantly important in the developments of high-performance and novel dielectric elastomers. In this work, we fabricated a series of aliphatic polyurethane elastomers (PUEs) based on hydroxyl-terminated butadiene-acrylonitrile copolymer (HTBN), hexamethylene diisocyanate (HDI), and various lengths of linear aliphatic diols and investigated effect of their microstructure and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 35 publications
(57 reference statements)
0
28
0
Order By: Relevance
“…Since the hard domains (HDs) of TPUs are formed by ordered hydrogen bonded (Hbonded) hard segments, the CO groups of TPUs can be divided into four types based on the degree of hydrogen bonding. Those CO groups [28,29] include free CO, disordered H-bonded CO, ordered H-bonded CO, and ordered H-bonded CO in crystalline phase which are corresponding to bands at 1,730, 1,716, 1,704, and 1,690 cm −1 , respectively, as shown in Figure 2. The free CO groups are from SD, and the disordered H-bonded CO groups are from SD or the interphase between HD and SD.…”
Section: Microphase Separation Of Tpusmentioning
confidence: 99%
“…Since the hard domains (HDs) of TPUs are formed by ordered hydrogen bonded (Hbonded) hard segments, the CO groups of TPUs can be divided into four types based on the degree of hydrogen bonding. Those CO groups [28,29] include free CO, disordered H-bonded CO, ordered H-bonded CO, and ordered H-bonded CO in crystalline phase which are corresponding to bands at 1,730, 1,716, 1,704, and 1,690 cm −1 , respectively, as shown in Figure 2. The free CO groups are from SD, and the disordered H-bonded CO groups are from SD or the interphase between HD and SD.…”
Section: Microphase Separation Of Tpusmentioning
confidence: 99%
“…A large variety of elastomers, including silicone rubbers, 7 acrylic elastomers, 8 and thermoplastic polyurethanes (TPU) 9 have been applied to assemble DEA. Among them, TPU is a promising candidate due to its relatively high permittivity, great breakdown strength, easy processing, good biocompatibility, and low cost 5,10,11 . While a key limitation for the practical application is the requirement for high driven electric field ( E ) (>100 kV mm −1 ), 4,12,13 which is due to its poor actuation strain at a low electric field.…”
Section: Introductionmentioning
confidence: 99%
“…DAN4 shows a more pronounced increase in dielectric losses from a much lower temperature (−25 C) due to the Tween 20 structure, which has fewer constraints in achieving dipole polarization. 42 F I G U R E 1 1 Arrhenius plots ln(τ max ) versus 1000/T for the β relaxation of the (a) linear and (b) cross-linked poly(urethane-urea) [Color figure can be viewed at wileyonlinelibrary.com] T A B L E 6 Arrhenius parameters: Activation energy, E a , and pre-exponential factor, τ 0 , for secondary γ and β relaxations Previous studies have shown that the introduction of small amounts of dipole moieties, such as that of aromatic groups, on the main chain of the polymer results in increase dielectric permittivity. 54 The presence on the polymer main chain of urethane groups, small amounts of aromatic groups as well as methoxy groups grafted on the aromatic group, all these confer high polarity which results in high dielectric capacitance, as shown by the results in Figure 6 (ε 0 = 7.6 at 1 Hz and ε 0 = 5 at 10 6 Hz, obtained at −25 C).…”
Section: F I G U R Ementioning
confidence: 99%
“…39,40 The electrical properties of polyurethanes and poly(urethane-urea) are important and are studied in order to obtain intelligent polymeric materials with electrical properties determined by the frequency and intensity of the applied electric field. 7,41 Previous results 42,43 have indicated that the dielectric constant and the dissipation factor of the polyurethanes are dependent both on the orientation of the dipole of the hard and soft segments, but also on their microstructure. Dielectric spectroscopy is used for the investigation of the molecular dynamics of the polyurethanes and poly(urethane-urea) with polar structure in very broad range of frequencies.…”
Section: Introductionmentioning
confidence: 99%